The Comparison of Prediction Model of Lowering Rate Road Surface Damage Between RCI and SDI Method in Lumajang Regency - Afandi, Yulianata Halim; Koesoemawati, Dewi Junita; Hasanuddin, Akhmad (BERKALA SAINSTEK, 2021)
Sand mining was a non-metal mineral commodity which had very good quantity and quality for building materials in Lumajang district. It was found in lava routes or large rivers in the Pasirian sub-district at Lumajang district. The location of sand material was in a river that passes through the regency road. This result was in many road damage in the district area. The efforts to overcome the damage that often occurs on roads in Pasirian sub-district included road improvement activities supported by road surface surveys using the RCI method which has been used in reporting basic road conditions. This study aim conducted of comparing the RCI survey method and predicting a decline in the last 3 (three) years to 2021 with the SDI survey method in 2021. The value being compared was in good condition from the overall report. After predicting the reduction in road damage with the regression method from the survey results of road conditions in 2017 - 2020 with the RCI method, the equation Y = -11,807 x 2021 + 23868 has a prediction of a decrease of 6,053%. After carrying out a survey of road conditions used the SDI method in 2021 on district roads in the Pasirian sub-district. There was an 8% decrease in good conditions. On the road in the Pasirian regency area, the decrease in the condition of the road surface was due to one of the factors being the excessive traffic load (over loaded) which causes a steady condition of the sections around the sand mine in the Pasirian sub-district.